Effects of Access Database Management System Hands-on Experience on Students’ Academic Achievement and SelfEfficacy in Database Management - Joseph. C. (PhD), Onuoha; Michael I, Onyepunuka; Orie (PhD), Idika Ezinne; Fumnanya, Ekwesaranna; Chukwuma (PhD), Emmanuel (International Journal of Psychosocial Rehabilitation, 2021)
The purpose of this study is to determine the effect of access database management system’shands-on experience on students’ achievement, interest and self-efficacy in databasemanagement in economics education. Quasi-experimental design specifying pre-test post-testcontrol group design was adopted. The sample size was 72 students from two purposivelyselected intact classes. Simple random sampling technique was used to assign the classes, one tocontrol group and the other to the experimental group. Three research questions and two nullhypotheses were formulated to guide the study. Validated and trial-tested Databank ManagementAchievement Test (DMAT) was used for data collection for both the pretest and posttest whileValidated Databank Management Interest Inventory (DMII) and Databank Management SelfEfficacy Scale (DMSS) were used to collect data on students’ interest in Databank Managementand students’ self-efficacy belief in Databank Management respectively. Mean and standarddeviation were used to answer research questions and analysis of covariance used to test the nullhypothesis at 0.05 probability level. The result proved that Access Hands-on Experienceapproach is more efficacious in enhancing students’ achievement, interest and self-efficacybelieve in Databank Management than the lecture method. It was recommended that Hands-onExperience should be encouraged in teaching Databank Management in tertiary institutions andthat its use should be popularized through workshops, seminars and conferences